Recycling of Organic Solid Wastes of Cities to Biofertilizer Using Natural Raw Materials - Hussian, Abid S; Hyder, Nadhem H; Braesam, Tarif H; Natheer, Adel M (Al-Nahrain Journal of Science, 2018)
A pilot composting system was conducted at the factory of recycling of organic solid wastes in Al-Usifia near Baghdad city, to investigate the possibility of the conversion organic fraction of Municipal organic solid waste (OFMSW) to biofertilizer. Results of MSW analysis showed the presence of 64% of biodegradable organic matter and 36% non-biodegradable. The initial composition of OFMSW had a high C/N ratio 37.02, and low availability N content. The additives used in OFMSW composting such as Buffalo, chicken and sewage sludge to the compost pile to treat N deletion and to obtain a desirable C/N ratio in treating piles. Various parameters were determined during the composting process of OFMSW and mixtures, to evaluate their suitability as indicators for the composting process. Results showed that after 6-10 weeks of incubation, the OFMSW turned to black-like substances with earthy smelling compost material. The pH of the mature compost ranged from 7.8 to 7.89; EC in all piles ranged from 3.11 to 5.41 dS/m. The N% increased with time in all piles reaching at the end of maturation to 1.04 to 1.84, the total phosphorous was high in all piles and varied from 1.11 to 1.6% in all piles. However, the results also revealed a higher potassium concentration varied from 1.18 to 3%, compared to initial concentration ranged from 0.6 to 1.6 in all piles. The water holding capacity of compost samples in all piles increased during composting and varied from 69 to 90% compared to initial ratio ranged from 14 to 45%. The windrow system was more effective for heavy metal marinating. The temperature in piles 2, 3 and 4 increased rapidly above 50°C for 4 weeks and reached to the peak recorded value of more than 60°C indicating higher degradation rate, while the temperature in pile 1 and 5 increased slowly relative to the other piles. The biodegradation of organic wastes, as indicated obviously by the reduction of C/N ratio, was rapid and decreased from 27.4 – 37.02 to 9.47 – 15.26 after 6 weeks of composting. Total viable count in all piles showed a marked increase in initial composting process when the temperature increased and a marked decrease at the end of maturation. The total number of bacteria in Piles 2, 3 and 4 was higher than in Piles 1 and 5. Coliform bacteria were found till 6 weeks in piles 2, 3 and 4, while recording up to 10 weeks in piles 1 and 5. Salmonella and Shigella did not appear throughout the study after 6 weeks of incubation, with exception in piles 1 and 5; these organisms were detected till weeks 10 to 14. Total fungi count decreased in piles 2, 3 and 4 when the temperature increased from 52°C to 60°C, while continued to increase till the end of maturation when the temperature fell to 30°C. Total fungi count recorded at the end of maturation was higher than the initial stage. Physiochemical and microbial characteristics of the final compost product could be recommended that the OFMSW is suitable for composting using the turning windrows system.